Safety and immunogenicity of high molecular weight polysaccharide vaccine from immunotype 1 Pseudomonas aeruginosa. - Pier, G B (1982)
The safety and immunogenicity of a high molecular weight polysaccharide from immunotype 1 Pseudomonas aeruginosa were tested in a dose response fashion in adult volunteers. The vaccine lacked toxicity and pyrogenicity for experimental animals. Doses of 50, 75, 150, or 250 microgram were given to groups of individuals as a single dose subcutaneous injection. Doses of 150 and 250 microgram were associated with a significant rise in binding and opsonic antibody at 2 wk postimmunization. Titers remained unchanged for up to 6 mo. The vaccine was almost devoid of toxicity, eliciting no more than a slightly sore and tender arm at the site of injection. High molecular weight polysaccharide antigen appears to induce a good immune response following vaccination that is effective in mediating opsonophagocytic killing of live P. aeruginosa organisms.